Metaphors are Embodied, and so are Their Literal Counterparts - Santana, Eduardo; De Vega, Manuel (Frontiers in Psychology, 2011)
This study investigates whether understanding up/down metaphors as well as semantically homologous literal sentences activates embodied representations online. Participants read orientational literal sentences (e.g. she climbed up the hill), metaphors (e.g. she climbed up in the company), and abstract sentences with similar meaning to the metaphors (e.g. she succeeded in the company). In Experiments 1 and 2, participants were asked to perform a speeded upward or downward hand motion while they were reading the sentence verb. The hand motion either matched or mismatched the direction connoted by the sentence. The results showed a meaning-action effect for metaphors and literals, that is faster hand motion responses in the matching conditions. Notably, the matching advantage was also found for homologous abstract sentences, indicating that some abstract ideas are conceptually organized in the vertical dimension, even when they are expressed by means of literal sentences. In Experiment 3, participants responded to an upward or downward visual motion associated with the sentence verb by pressing a single key. In this case, the facilitation effect for matching visual motion-sentence meaning faded, indicating that the visual motion component is less important than the action component in conceptual metaphors. Most up and down metaphors convey emotionally positive and negative information, respectively. We suggest that metaphorical meaning elicits upward/downward movements because they are grounded on the bodily expression of the corresponding emotions.